Razka Pustaka and Digital Transformation: Islamic Book Publishing Strategies in the Industrial Era 4.0 - Mohammad Nurul Yaqin; Sedya Santosa (Communigate, 2025)
The development of digital technology has had a significant impact on the book publishing industry, including for Islamic book publishers such as Razka Pustaka. With the presence of e-commerce, social media, and print-on-demand technology, Razka Pustaka is faced with the need to carry out digital transformation in order to maintain the continuity and develop its business in the industry 4.0 era. This study aims to analyze the digital transformation strategy implemented by Razka Pustaka, including the initiatives undertaken, challenges faced, and impacts caused. Using a qualitative case study approach, data was obtained through in-depth interviews, observations, and document analysis. The results of the study show that Razka Pustaka has implemented various digital strategies such as digitalization of the publishing process, development of an online sales platform, and marketing through social media to expand market reach. In addition, the application of automation technology and integration of internal management systems has increased operational efficiency. The impacts of this digital transformation include increased productivity, time efficiency, and wider market expansion, both domestically and abroad. This study is expected to provide insight for other Islamic book publishers in developing business strategies that are more adaptive to changes in digital technology.